Three decades of health financing study: did Malaysia learn anything? - Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2014)
Health care is everyone‟s right, it is the government‟s responsibility to provide health care system which is equitable to the population. Malaysia‟s dualism of health care system, of a heavily subsidized public sector and out-of-pocket financing of private sector, has produced a progressive system of health care. Malaysia‟s health care system has provided remarkable equity and access; considering the government devotes less of its gross domestic product (GDP) to the health care than other industrialized countries.However new challenges have emerged; disease pattern and population profiles are changing, there is growth in the private health care sector, high proportion of health care expenditure comes from out-of-pocket, and increased demand for high quality and high-cost of medical technology. All these have forced the government to consider the need of restructuring the health care financing mechanism of the country. Over the last three decades the Government of Malaysia has been considering and reviewing various health‟s financing mechanism aimed at reforming the country health financing mechanism in order to strengthen the national health care system. This is not only addresses the challenges and issues faced by the country health care system, but also aligns its development to the aspiration of the country in becoming a high income economy by the year 2020.There are studies recommending various health financing mechanisms such as national health insurance, medical savings account, and social health insurance. The controversial 1Care reform proposed by the Ministry of Health is the latest attempt by government to restructure Malaysia‟s health care system in particular health care financing mechanism. Lack of consultation with stakeholders, commitment, support and understanding amongst politicians (government and opposition) as well as health care providers and other interested parties, lack of evidence for the proposals, lack of legal-framework to back-up the initiatives, and the lack of effort by government to educate Malaysian population on the necessity of health care financing reform in the last three decades have resulted in the initiative not being well received. The aimed of this review is to analyse experiences and lessons learned from various health care financing initiatives carried out by the Malaysian Government for the last three decades.